Peningkatan Kesejahteraan Emosional Santri Melalui Praktik Mindfulness dan Refleksi Spiritual - Nisa, Khoirun (FKIP Universitas Islam Jember, 2024)
Pesantren play a pivotal role in shaping the character of young generations, yet students often face emotional pressures that affect their well-being. This study aims to evaluate the effectiveness of a mindfulness and spiritual reflection program in enhancing the emotional well-being of pesantren students. Using a quasi-experimental design with pretest-posttest and a control group, 60 students were divided into a treatment group (n = 30) and a control group (n = 30). The eight-week intervention included mindful breathing, meditation, dzikir, and reflective discussions. Results showed a significant increase in the Warwick-Edinburgh Mental Well-being Scale (WEMWBS) scores for the treatment group from 45.2 to 61.8 (p < 0.001), while no significant change was observed in the control group (p = 0.47). Qualitative findings supported the program's effectiveness in emotion regulation and strengthening spirituality. This program holds potential for adaptation in various cultural and religious communities.